A Journey in Science: "Not Lost in Translation" - Tak Mak (BMC, 2016)
Abstract Real innovations in medicine and science are historic and singular; the stories behind each occurrence are precious. At Molecular Medicine we have established the Anthony Cerami Award in Translational Medicine to document and preserve these histories. The monographs recount the seminal events as told in the voice of the original investigators who provided the crucial early insight. These essays capture the essence of discovery, chronicling the birth of ideas that created new fields of research; and launched trajectories that persisted and ultimately influenced how disease is prevented, diagnosed, and treated. In this volume, the Cerami Award Monograph is by Tak Mak, PhD, Professor, The Campbell Family Institute for Breast Cancer Research, Ontario Cancer Institute, Princess Margaret Cancer Centre in Toronto. A visionary in the field of cancer, this is the story of Dr. Mak's scientific journey.